Canadian Codes of Medical Ethics as a Source of Law - Lytvynenko, Anatoliy A.; Petlina, Tetiana V. (Teisė, 2024)
The article discusses the codes of medical ethics which are adopted in Canada. These acts are not ‘classical’ normative-legal acts, since they are adopted not by legislative bodies, but rather by medical associations, and are aimed at providing rules on the professional conduct of physicians and auxiliary medical personnel; occasionally, they also feature the rules concerning the rights and duties of patients. The article’s sources include the codes of medical ethics adopted in Canada, Canadian court judgments, and academic literature.
Keywords: Code of Medical Ethics; Medical Law; Canadian Law; history of Law; legal theory